2022
DOI: 10.1016/j.ultsonch.2022.105914
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonics as a tool for development of pine-needle extract loaded bee wax edible packaging for value addition of Himalayan cheese

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…In all samples, during 30 days of ripening, the level of yeast and mold had a decreasing trend ( p < .05). The antimicrobial activity of the cheese could be related to the peptides produced during cheese fermentation by proteolytic enzymes (Joseph‐Leenose‐Helen et al., 2022 ). The YMC reduction trend was much higher in the treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…In all samples, during 30 days of ripening, the level of yeast and mold had a decreasing trend ( p < .05). The antimicrobial activity of the cheese could be related to the peptides produced during cheese fermentation by proteolytic enzymes (Joseph‐Leenose‐Helen et al., 2022 ). The YMC reduction trend was much higher in the treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…This showed the preservative effect of the coating on moisture retention. The coated cheese was also more cohesive during storage (Joseph‐Leenose‐Helen et al., 2022). Cucumber peel EX and cumin, basil, rosemary, artemisia, and mint EOs showed a similar trend limiting the moisture loss and hardness reduction of ultrafiltered and homemade cheeses (Ahmadimaram & Mostaghim, 2021; Esparvarini et al., 2022; Mahcene et al., 2021).…”
Section: Application Of Edible Coatingsmentioning
confidence: 99%
“…The application of pine‐needle EX in edible coating to preserve Himalayan cheese showed significantly higher scores for appearance and texture, especially when increasing the amount of EX. In contrast, flavor and taste showed lower values, probably due to the typical smell of pine needles (Joseph‐Leenose‐Helen et al., 2022). Similarly, cucumber peel EX and cumin EO incorporated in gelatin‐starch coating resulting an increase of all attributes of sensory analysis (Esparvarini et al., 2022).…”
Section: Application Of Edible Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although polyphenols have strong functional activity, polyphenols themselves are not stable and usually require other auxiliary means to bind to proteins to play a greater role, as a green treatment method, ultrasonic wave has been widely used in the treatment of raw materials for active packaging. In the study of Jenno et al [117] , ultrasonic treatment of beeswax of pine needle extract (PNE) significantly improved the antioxidant, anti-diabetic and antibacterial activities of PNE packaging self-coating. Kumar et al [118] showed that the performance of beeswax-clove essential oil film was enhanced after ultrasonic treatment and Zhen et al [119] reviewed natural protein-based natural antibacterial materials and their applications in food preservation in recent years.…”
Section: The Effect Of Multi-field Combination Of Ultrasound On the A...mentioning
confidence: 99%